A Tool for Generating a Symbolic Representation of tccp Executions - Lescaylle, Alexei; Villanueva, Alicia (Electronic notes in theoretical computer science, 2009)
The Timed Concurrent Constraint language (tccp) was defined by F. de Boer et al. as an extension of the Concurrent Constraint Paradigm (Saraswat, 1993) for specifying reactive and embedded systems. In this paper, we describe the StructGenerator system which, given the specification of a tccp program, constructs a symbolic representation (a tccp Structure) modeling the behavior of such tccp program. The resulting structure allows one to verify the program by using a model-checking algorithm. It is similar to a Kripke Structure but, due to the nature of the ccp model, it differs from the classical approach in some important points that will be described along the paper. The StructGenerator system, implemented in C++, takes as input a file containing the specification of a tccp program and generates the associated tccp Structure. Along the paper, we cover the design and implementation of StructGenerator. We also demonstrate its functionality carrying out the execution of two practical examples.